Spin Seebeck effect in quantum dot side-coupled to topological superconductor. (23rd January 2017) - Weymann, Ireneusz
Abstract: The spin-resolved thermoelectric transport properties of a quantum dot coupled to ferromagnetic leads and side-coupled to a topological superconductor wire hosting Majorana zero-energy modes are studied theoretically. The calculations are performed in the linear response regime by using the numerical renormalization group method. It is shown that transport characteristics are determined by the interplay of Kondo correlations, exchange field due to the presence of ferromagnets and the strength of coupling to Majorana wire. These different energy scales are revealed in the behavior of the Seebeck and spin Seebeck coefficients, which exhibit an enhancement for temperatures of the order of the coupling strength to topological wire. Moreover, it is demonstrated that additional sign changes of the thermopower can occur due to the presence of Majorana zero-energy modes. These findings may provide additional fingerprints of the presence of Majorana fermions.